A chromogenic and fluorogenic peptide substrate for the highly sensitive detection of proteases in biological matrices - Arian, Dumitru; Harenberg, Job; Krämer, Roland (Journal of medicinal chemistry, 2016)
The synthesis and application of a novel type of chromogenic and fluorogenic substrate for protease detection is described. The outstanding performance of the tripeptide substrates is exemplified by specific fluorescence detection of thrombin and factor Xa at only 500 fM concentration. The substrate is also applicable to the sensitive detection of the thrombin inhibitor dabigatran in human plasma and whole blood samples, highlighting its potential for a point-of-care test for instant monitoring the blood levels of this blockbuster anticoagulant drug in specific clinical situations.